Pengorganisasian Masyarakat Desa Besuki untuk Meningkatkan Kesadaran terhadap Lingkungan dengan Pengelolaan Sampah - Ardeya Windyana; Camaylia Ika Putri; Ezra Febriana Sitanggang; Ni’amil Ridha Maula; Rahillailia Khoirunnisa; Ulin Ismiatul Mutmainah; Ratna Endang Widuatie (Cakrawala: Jurnal Pengabdian Masyarakat Global, 2023)
Besuki is an urban village with total population approximately 14.000 inhabitants. one of the biggest problem in Besuki is garbage. overcrowding in Besuki is leading to more garbage production. Most of the people in Besuki still dispose of garbage carelessly such as in the river, house yard, or roadside ditch. Garbage problems in the society includes organic garbage and inorganic garbage. Organic garbage will be processed into fertilizer and compasses, while inorganic garbage will be used as craft materials (ecobricks). The methods used in this work program are approach, assessment, brainstorming, formation, and monitoring evaluation. With the counseling and direct practice, it is hoped that the community can process and utilize waste properly and can be used as a business opportunity.